KARAKTERISTIK PENDIDIKAN AGAMA ISLAM PADA LEMBAGA PENDIDIKAN - Ishak Ishak (FiTUA: Jurnal Studi Islam, 2021)
Islamic Religious Education is also a conscious and planned effort in preparing students to recognize, understand, live, to believe, be pious, and have noble character. As for the basis of Islamic Religious Education is the Qur'an and Hadith. The purpose of Islamic Religious Education is to foster religious people, which means humans who are able to carry out the teachings of the Islamic religion properly and perfectly, so that they are reflected in attitudes and actions in all their lives. The characteristics of Islamic religious education are those that refer to definite rules, consider two sides of life, namely the world and the hereafter, have the mission of moral formation, are believed to be sacred tasks and serve as worship.